2009
DOI: 10.1007/s10616-009-9191-2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative and apoptotic effects of oleuropein and hydroxytyrosol on human breast cancer MCF-7 cells

Abstract: Olive oil intake has been shown to induce significant levels of apoptosis in various cancer cells. These anti-cancer properties are thought to be mediated by phenolic compounds present in olive. These beneficial health effects of olive have been attributed, at least in part, to the presence of oleuropein and hydroxytyrosol. In this study, oleuropein and hydroxytyrosol, major phenolic compound of olive oil, was studied for its effects on growth in MCF-7 human breast cancer cells using assays for proliferation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
210
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(242 citation statements)
references
References 26 publications
8
210
1
5
Order By: Relevance
“…3). These results are in line with other studies that have reported that olive oil, oleic acid and minor compounds of olive oil can modulate apoptosis (51,(75)(76)(77) . Apoptosis is a crucial process in cancer development, and it has been suggested that tumour growth is partly determined by the balance between cell proliferation and apoptosis.…”
Section: Influence On Signalling Pathwayssupporting
confidence: 93%
“…3). These results are in line with other studies that have reported that olive oil, oleic acid and minor compounds of olive oil can modulate apoptosis (51,(75)(76)(77) . Apoptosis is a crucial process in cancer development, and it has been suggested that tumour growth is partly determined by the balance between cell proliferation and apoptosis.…”
Section: Influence On Signalling Pathwayssupporting
confidence: 93%
“…Epidemiological studies have shown that the incidence of atherosclerosis, cardiovascular diseases and certain types of cancer is lower in the Mediterranean area than in other areas (1,2). The lower rate of large bowel, breast, endometrial, as well as prostate cancers, described by a number of epidemiological studies, besides possible genetics factors, is also attributed to the characteristic type of diet of the local population.…”
Section: Introductionmentioning
confidence: 99%
“…Since these leaves contain many potentially bioactive compounds, they may have antioxidant properties (El and Karakaya 2009;Moussaoui et al 2010). At the same time olive leaves have been heavily exploited for the prevention or the treatment of hypertension, carcinogenesis, diabetes, atherosclerosis, gingivitis and many other traditional therapeutic uses (Han et al 2009;Haloui et al 2010;Bouallagui et al 2011). Poudyal et al (2010) reported that olive leaf extract (OLE) containing polyphenols such as oleuropein and hydroxytyrosol reversed the chronic inflammation and oxidative stress by diet-induced obesity and diabetes in cardiovascular, hepatic, and metabolic symptoms in rats.…”
Section: Introductionmentioning
confidence: 99%